Ranking of Factors Affecting Self-Esteem and Body Image Dissatisfaction in Adolescents with Eating Disorders - Gorji Azandariyani, Hossein; Shakerinia, Iraj; Hosseinzadehmahdavi, Masoumeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective:   This study aimed to identify and rank the key psychological, familial, social, and cultural factors influencing self-esteem and body image dissatisfaction among adolescents with eating disorders.Methods and Materials: The research employed a mixed-method sequential exploratory design consisting of qualitative and quantitative phases. In the first phase, a systematic literature review was conducted to extract and code relevant factors until theoretical saturation was achieved. The qualitative data were analyzed using thematic content analysis in NVivo 14, resulting in seven major thematic categories: psychological factors, family environment, peer and social comparison, media and cultural influences, sociocultural expectations, coping and self-compassion, and physical and health awareness. In the second phase, a structured questionnaire derived from these qualitative findings was administered to 20 adolescents with eating disorders in Tehran, selected through purposive sampling. The collected quantitative data were analyzed using SPSS version 26, and the Friedman test was applied to determine the ranking of factors influencing self-esteem and body image dissatisfaction.Findings: Results showed significant differences among the ranked factors (p < 0.05). Psychological factors obtained the highest mean importance score (M = 4.82, SD = 0.21), followed by family environment (M = 4.56, SD = 0.28), peer and social comparison (M = 4.31, SD = 0.35), and media and cultural influences (M = 4.17, SD = 0.33). Lower-ranked factors included sociocultural expectations (M = 3.92, SD = 0.41), coping and self-compassion (M = 3.74, SD = 0.46), and physical and health awareness (M = 3.58, SD = 0.50). These inferential results confirmed significant prioritization across domains affecting adolescents’ self-esteem and body image.Conclusion: The study highlights the primacy of psychological and familial determinants over environmental or health-related factors in shaping body image and self-esteem among adolescents with eating disorders. These findings suggest that future interventions should integrate emotion regulation, family communication, and self-compassion training into prevention and treatment frameworks.